(3OhQ GdYQa ceUOQ ddbGYOI GdbGfhfjI aj GdbGfhf GdQheGfj hGdTQjYI GdESdGejI (B: s (3OQGSI ebGQfI (B/ s - (3EjgGH YHGS YHO GdaJGM GdaQGTs; (3Uhaj CHh WGdH (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B:s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI(B.s, 2006)
(3ai Xd JbfjGJ Ydhe GdaVGA hGdaVGFjGJ hKhQI GdGJUGdGJ VYaJ GdahGUd GdGbdjejI hGUHM GdYGde bQjI UZjQI (B: (3adG jSJWjY eLJeY Gf jZdb GHhGHg Gh jJbhbY Ydi faSg (B: (3hdcf JOGNdJ GdKbGaGJ hGdMVGQGJ hJWhQJ GdGacGQ hGdYGOGJ ai GdGYQGa (B: (3hXgQJ GQGA JfGOi hJOYhG (B- (3Ydi MO bhdge (B- (3Gdi JLOjO Gdabg GdGSdGei ddMGb HQcH GdeOfjI GdMOjKI ai MjGJfG GdeYGUQI (B: (3acGf dRGeG Gf fba dfXgQ ehba GdTQjYI GdGSdGejI ef JWhQ GdMjGI hJWhQ YGOGJ hGYQGa GdfGS JHYG dPdc (B: (3hfHjf gd jMJGL Gdabg GdGSdGei (B- (3ceG jOYh GdHYV (B- (3Gdi JLOjO Ge dOjg GdbOQI GdPGJjI Ydi ehGcHI gPGdJWhQ hGdGfSLGe GdWHjYi eY eJZjQGJ GdMjGI (B: (3hPdc ai Xd OQGSI OhQ GdYQa ai GdTQjYI GdGSdGejI (B: (3eMGhdjf (B- (3HGdGVGaI Gdi Pdc (B- (3Gf fJYQa Ydi JLQHI GdbGfhf GdQheGfi GdPi YGUQ hTgO GdcKjQ ef GdGYQGa eY cKQI GdHdOGf GdJi cGfJ JGHYI ddGeHQGWhQjI GdQheGfjI (B0s
(3jTJed Ydi edGMb UaMGJ (B381 - 412.s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe adSaI GdbGfhf h JGQjNgs
(3jTJed Ydi EQLGYGJ HHdjhLQGajI UaMGJ (B414 - 431.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3adSaI GdbGfhf hJGQjNgs; (3eUOQ GdbGYOI GdbGfhfjIs; (3GdTQjYI GdESdGejIs; (3GdbGfhf GdQheGfjs; (3GdbhGfjf GdZQHjI GdbOjeIs; (3GdbhGfjf GdTQbjI GdbOjeIs; (3GdHQjJhQs; (3GdePGgH GdabgjIs; (3Gdabg GdeHfj Ydi GdYQas; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs